2000
DOI: 10.1159/000008139
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia of Single Tool Use

Abstract: We report a 72-year-old right-handed man who showed an ‘apraxia of tool use’ after a cerebral infarct in the territory of the left middle cerebral artery. His apraxia of tool use was characterized by a clear dissociation between the inability to use a single tool and the ability to use plural tools. Most of the errors occurred in selecting an appropriate target where a tool is expected to be applied. Detailed examinations confirmed that his conceptual knowledge of tool use was well preserved. Furthermore, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Partial and elementary actions were maintained, but there were various errors in the movements he appeared to perform correctly. In the present study, five types of 10 patterns of errors were identified, based on two classifications by De Renzi and Lucchelli [6]and Hayakawa et al [10](table 2). First, he made errors in the relation between a hand and a tool.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Partial and elementary actions were maintained, but there were various errors in the movements he appeared to perform correctly. In the present study, five types of 10 patterns of errors were identified, based on two classifications by De Renzi and Lucchelli [6]and Hayakawa et al [10](table 2). First, he made errors in the relation between a hand and a tool.…”
Section: Resultsmentioning
confidence: 99%
“…De Renzi and Lucchelli [6]reported that in 20 left-brain-damaged patients performance in the single-object test was highly correlated with that in the multiple-object test. Recently Yamadori [9]and his colleagues have proposed the descriptive term of ‘apraxia of single-tool use’, based on their encounter with a rare case in which the ability to demonstrate the use of a single tool was disproportionally impaired [10]. Nevertheless, there have been few analyses of single-tool use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hayakawa et al (2000) described an individual exhibiting a dissociation between the inability to use single tools and the ability to use a series of tools (e.g. make a cup of tea).…”
Section: Execution Of Transitive Gestures Involving a Single Toolmentioning
confidence: 99%